2022
DOI: 10.1021/acsestwater.2c00060
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Surveillance of SARS-CoV-2 at a Canadian University Campus and the Impact of Wastewater Characteristics on Viral RNA Detection

Abstract: Because of the increased population density, high-risk behavior of young students, and lower vaccination rates, university campuses are considered hot spots for COVID-19 transmission. This study monitored the SARS-CoV-2 RNA levels in the wastewater of a Canadian university campus for a year to provide actionable information to safely manage COVID-19 on campus. Wastewater samples were collected from the campus sewer and residence buildings to identify changes, peaks, and hotspots and search for associations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…Fraternities may be factored into the analysis due to the correlation between males and the presence of fecal viruses (Daou et al 2022). This correlation is consistent with the research conducted by Bitter et al (2022), wherein the university was identified as a microcosm of the corresponding city and exhibited analogous trends in COVID-19 cases.…”
Section: Discussionsupporting
confidence: 89%
“…Fraternities may be factored into the analysis due to the correlation between males and the presence of fecal viruses (Daou et al 2022). This correlation is consistent with the research conducted by Bitter et al (2022), wherein the university was identified as a microcosm of the corresponding city and exhibited analogous trends in COVID-19 cases.…”
Section: Discussionsupporting
confidence: 89%
“…Wastewater monitoring at upstream sites may act as mirrors of trends within the community ( Supplementary Figure S2 ) ( 50 , 51 ). Additionally, variant-specific assays as well as sequencing of variants within upstream sites can provide insight about variants of SARS-CoV-2 within the larger population.…”
Section: Resultsmentioning
confidence: 99%
“…Neighborhood-scale monitoring for COVID-19 has been conducted (Barrios et al, 2021;Spurbeck et al, 2021). While this neighborhood-scale monitoring could allow for a more targeted public health intervention in a specific community, SARS-CoV-2 N gene concentrations presented lower correlation coefficients with COVID-19 infection cases as the catchment populations decreased (Bitter et al, 2022;Rusiñol et al, 2021;Sangsanont et al, 2022).…”
Section: Introductionmentioning
confidence: 99%